Cancer in pregnancy. Part I: basic diagnostic and therapeutic principles and treatment of gynecological malignancies - Hoellen, Friederike; Hornemann, Katrin Emma; Hornemann, Amadeus (Archives of gynecology and obstetrics, 2012)
PurposeCancer in pregnancy is a rare circumstance. However, the coincidence of pregnancy and malignancy is supposed to increase due to a general tendency of postponing childbearing to older age. To date, clinical guidelines are scarce and experience regarding therapeutic management is limited to case reports.MethodsThis review focuses on general diagnostic and therapeutic principles including systemic therapy for malignancies in pregnancy.ResultsIn part I, we report on diagnosis and therapy of gynecological tumors.ConclusionThe diagnosis of gestational cancer faces both oncologist and obstetrician to the dilemma of applying appropriate diagnostic techniques and adequate local and systemic therapy to an expectant mother without harming the fetus.
First online: 20 August 2011
Gesehen am 25.04.2018